Formulation Development and Evaluation of Sustained Release Bioadhesive Bilayered Buccal Tablets of Furosemide. Issue 2 (4th March 2017) - Daravath, Bhaskar; Swathi, D.; Rao, B. Babu
Abstract: The aim of the present investigation was to develop bioadhesive bilayered buccal tablets of furosemide. The tablets were directly compressed using various biooadhesive polymers like chitosan, hydroxypropyl methylcellulose (HPMC), carbopol-934 and sodium carboxy methylcellulose (sodium CMC) in different ratios and also in combination of two polymers. Ethyl cellulose (EC) was used as impermeable backing layer. Buccal tablets were evaluated for several parameters such as thickness, hardness, weight uniformity, drug content uniformity, surface pH, swelling index, in vitro drug release, ex vivo permeation studies and stability studies were conducted in human saliva. Drug-polymer compatibility studies were conducted by FTIR (Fourier Transform Infrared Spectroscopy). The optimised formulation F9 (chitosan and sodium CMC at the ratio of 40:40) showed good swelling and almost neutral pH. The optimized formulation F9 has good bioadhesive strength and ability to sustain the release of drug in 8 hours (99.84±1.47 %) and it was found to be non-Fickian. FTIR study revealed there was no interaction between drug and polymer. Stability studies of optimised formulation indicate the drug was stable in human saliva for 8 hours. Hence, the formulation of bioadhesive bilayered buccal tablets using bioadhesive polymers can able sustained the release of furosemide for buccal delivery.